Unilateral Divorce, the Decreasing Gender Gap, and Married Women's Labor Force Participation - Fernández, Raquel; Wong, Joyce (American Economic Review, 2014)
Married women's labor force participation (LFP) increased dramatically in the United States between the 1940 and 1960 cohort. The two cohorts lived under different divorce regimes (unilateral divorce rather than mutual consent). The 1960 cohort also had a lower gender wage gap. We use a quantitative dynamic life-cycle model of endogenous marital status, calibrated to key statistics for the 1940 cohort, to study the effects of these two changes. We find that both drivers combined are able to account for over 50 percent of the increase in married women's LFP and also generate large movements in marriage and divorce rates.